2011
DOI: 10.5539/jsd.v4n6p23
|View full text |Cite
|
Sign up to set email alerts
|

Transport Infrastructure Investment and Sustainable Economic Growth in Côte d’Ivoire: A Cointegration and Causality Analysis

Abstract: This study examines the temporal relationship between transport infrastructure investment and output in Côte d'Ivoire over the period . Using cointegration and causality tests within a multivariate framework, it is found that the public investment in transport infrastructure, private investment and economic output are cointegrated. The results of the Granger causality tests reveal that public investment in transport does not have a causal impact on economic growth; conversely economic growth has a causal impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In terms of methodology, this study is based on a spatial interaction analysis by employing a gravity model framework, differentiating from the mainstream line of research in the field using mainly causality examinations such as Saidi et al (2018), Pradhan & Bagchi (2013), Badalyan et al (2014), Keho & Echui (2011), Mohmand et al (2017, Pradhan (2010) and He et al (2021). In that way, we incorporate spatial dimension of logistics infrastructure in the analysis.…”
Section: Literature Review and Significance Of The Studymentioning
confidence: 99%
“…In terms of methodology, this study is based on a spatial interaction analysis by employing a gravity model framework, differentiating from the mainstream line of research in the field using mainly causality examinations such as Saidi et al (2018), Pradhan & Bagchi (2013), Badalyan et al (2014), Keho & Echui (2011), Mohmand et al (2017, Pradhan (2010) and He et al (2021). In that way, we incorporate spatial dimension of logistics infrastructure in the analysis.…”
Section: Literature Review and Significance Of The Studymentioning
confidence: 99%
“…Researchers have also studied the causal relationship between transportation facilities and the economy with four categories of relationships. The first category is unidirectional, with transport facilities leading to economic growth [8][9][10][11], or economic development leading to the construction of transport facilities [12][13][14]. The second category is bidirectional causality among transportation facilities, including cargo transportation and economic growth [15][16][17].…”
Section: Consideration Of Previous Studiesmentioning
confidence: 99%
“…The coordination between varied freight modes (highway, rail, water, and aviation) and economic development can be calculated using Equations (11) and (12). The coordination results for the Eastern, Central, Western, and Northeast regions in 2010, 2012, 2015, and 2017 are shown in Table 13.…”
Section: Global Spatial Autocorrelationmentioning
confidence: 99%
“…These are the works of Banister and Berechman 2001;Boopen, 2006;Cantos et al (2005), Demetriades and Mamuneas, (2000), Khanam (1999), Escribano et al (2008, Garcia-Mila and McGuire (1992) and they have emphasized that road infrastructure has a negative effect. Also, a study by Keho and Echui (2011) showed that despite the existence of a causal relationship, there is no effect of transport infrastructure on economic growth in the case of Côte d'Ivoire.…”
Section: Introductionmentioning
confidence: 99%